Artificial Seed Production of Lobe Lia Chinensis Lour - Thong, Weng Hing (INTI University College, 2010)
An efficient protocol was developed for production of the artificial seed of Lobelia chinensis Lour. In vitro nodal segments of L. chinensis were used as inclusion materials for artificial seeds by entrapping them in various combinations of sodium alginate and calcium nitrate. The artificial seed was produced by mixing 3.5% sodium alginate and 50 mM calcium nitrate, supporting the optimal in vitro conversion potential. The number of shoots produced by encapsulated nodal segments was 3.4 while non-encapsulated nodal segments produced 3.5 shoots per explant. Plantlets regenerated from the artificial seeds of nodal segments were hardened, acclimatized and established well in the field, showing similar morphology with donor plants. This encapsulation technology would provide an easy and novel propagation system for L. chinensis.